Leveraging Mobile Communication App to Enable off Classroom Learning-Anatomy - Kate Deepali R (Academia Anatomica International, 2020)
Introduction:The study of Medicine is one of the primarily taxing and tedious disciplines of study. Aassimilation of intense knowledge and acuminating various skills in a short tenure is one of the challenges faced by students making learning more by rote, short-term and exam oriented. This study intended to explore an alternative innovative method for ensuring off classroom teaching-learning process. Aim and objectives: To study response of students towards learning with the aid of mobile communication app. To analyse both the impact of this teaching mode on self-directed learning and academic performance. To compare the academic performance of Blended Learning group with Traditional Learners.Subjects and Methods:Single observer interventional study was carried out among First year MBBS students. Group I students received traditional teaching (TL group n=80) while Group II students included Blended learners (BL group n=120) who received Traditional teaching and Mobile teaching. Both the groups were evaluated at periodic intervals by same assessment methods, mean of their academic scores were compared using t- test. In addition BL group was also administered an online questionnaire using five-point Likert scale to assess their perception with regards to the mobile teaching-learning process.Results:BL group students agreed that this mode of teaching-learning was beneficial encouraged them to read more than their regular also helped in developing their analytic skills. The academic results of the BL group though higher than TL group did not show statistical significant difference.Conclusion:This innovative method can be adapted in teaching other subjects at different levels of medicine curriculum.